The Radio-bright Accreting Millisecond X-Ray Pulsar IGR J17591-2342 - Russell, T.; Degenaar, N.; Wijnands, R.; Eijnden, J.; Gusinskaia, N.; Hessels, J.; Miller-Jones, James (Institute of Physics Publishing, 2018)
IGR J17591-2342 is a 527 Hz accreting millisecond X-ray pulsar that was discovered in outburst in 2018 August. In this Letter, we present quasi-simultaneous radio and X-ray monitoring of this source during the early part of the outburst. IGR J17591-2342 is highly absorbed in X-rays, with an equivalent hydrogen absorption along the line of sight, NH, of 4.4-1022 cm-2, where the Galactic column density is expected to be 1-2-1022 cm-2. The high absorption suggests that the source is either relatively distant (6 kpc), or that the X-ray emission is strongly absorbed by material local to the system. Radio emission detected by the Australia Telescope Compact Array shows that, for a given X-ray luminosity and for distances greater than 3 kpc, this source was exceptionally radio-loud when compared to other accreting neutron stars in outburst (LX1033 erg s-1). For most reasonable distances, IGR J17591-2342 appeared as radio luminous as actively accreting, stellar-mass black hole X-ray binaries.